Short-Term Ultraviolet (UV)-A Light-Emitting Diode (LED) Radiation Improves Biomass and Bioactive Compounds of Kale - Lee, Jin-Hui; Oh, Myung-Min; Son, Ki-Ho (Frontiers in Plant Science, 2019)
The aim of this study was to determine the influence of two types of UV-A LEDs on the growth and accumulation of phytochemicals in kale (Brassica oleracea var. acephala). Fourteen-day-old kale seedlings were transferred to a growth chamber and cultivated for 3 weeks. The kale plants were subsequently subjected to two types of UV-A LEDs (370 and 385 nm) of 30 W/m2 for 5 days. Growth characteristics were all significantly increased in plants exposed to UV-A LEDs, especially at the 385 nm level, for which dry weight of shoots and roots were significantly increased by 2.22 and 2.5 times, respectively, following 5 days of treatment. The Fv/Fm ratio began to decrease after 3 hours of treatment compared to the control. The total phenolic content of plants exposed to the two types of UV-A LEDs increased by 25% at 370 nm and 42% at 385 nm at 5 days of treatment, and antioxidant capacity also increased. The two types of UV-A LEDs also induced increasing contents of caffeic acid, ferulic acid, and kaempferol. The reactive oxygen species (ROS) increased in plants exposed to the two types of UV-A LEDs after 3 hours of treatment. Moreover, transcript levels of phenylalanine ammonia-lyase (PAL), chalcone synthase (CHS), and flavanone 3-hydroxylase (F3H) genes and PAL enzyme activity were higher in plants treated with UV-A LEDs. Our results suggested that short-term UV-A LEDs was effective in increasing growth and improving phytochemical content in kale thereby represents a potentially effective strategy for enhancing the production of phytochemicals.